1978
DOI: 10.1083/jcb.77.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated lipid alterations and their influence on the proliferation and fusion of cultured myogenic cells

Abstract: We have cultured myogenic cells derived from primary explants and a cell line (L6) in a lipid-depleted medium (LDM) and produced large alterations of the fatty acyl and polar headgroup composition and of the cellular sterol levels. These alterations were produced by altering the composition of the media as follows: removing biotin and providing exogenous fatty acid; removing choline and providing exogenous ethanolamine or choline analogues; and by adding 25-OH cholesterol, an inhibitor of 3-hydroxy-3-methylglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Fumagalli et al (8) have shown that membrane fusion does not take place in all areas of the closely apposed plasma membranes of rat myoblast, only in small spots were the two bilayers match and are able to proceed to fusion. By contrast, physicochemical studies of myoblast fusion have been interpreted as indicating that high lipid fluidity is essential for membrane fusion (10,11,12,22). In spite of the publication of these key observations, the mechanisms of membrane fusion are not well understood.…”
mentioning
confidence: 96%
“…Fumagalli et al (8) have shown that membrane fusion does not take place in all areas of the closely apposed plasma membranes of rat myoblast, only in small spots were the two bilayers match and are able to proceed to fusion. By contrast, physicochemical studies of myoblast fusion have been interpreted as indicating that high lipid fluidity is essential for membrane fusion (10,11,12,22). In spite of the publication of these key observations, the mechanisms of membrane fusion are not well understood.…”
mentioning
confidence: 96%
“…[7][8][9][10][11] In 1978, Horwitz et al 55 observed that the fatty acids added to the culture medium have a stimulatory effect on the fusion of embryonic myoblasts. The authors observed that the lipid composition of the membrane influences the proliferation and fusion of myoblasts and, consequently, the formation of multinucleated myotubes.…”
Section: Effects Of Fatty Acids On Muscle Cell Differentiationmentioning
confidence: 99%
“…Myoblasts were obtained from the pectoral muscle of 11-day chick embryos as in [13,14]. After digestion for 10 min in 0.1% dispase II (neutral protease from Bacillus polymyxa, Boehringer Mannheim Biochemicals) cells were plated on gelatin-coated 100 mm tissue culture dishes in calcium-free DMEM.…”
Section: Cellsmentioning
confidence: 99%
“…Fibroblasts were obtained from 11-day chick embryos as in [13]. The cells were maintained for 7-10 days and were subcultured at least twice during that time.…”
Section: Cellsmentioning
confidence: 99%